Outcomes of Intermediate Care Rehabilitation and Factors Associated with Functional Improvement of Post-Stroke Patient in Mueang Lopburi District, Lopburi Province - Angyureekul, Pornpun (Hua Hin Medical Journal, 2025)
Background: Cerebrovascular disease is a significant public health problem worldwide, including in Thailand. After surviving the critical phase, post-stroke patients require intermediate care (IMC) to enhance their ability to perform daily activities independently, reduce disability, and reintegrate into society. Objective: This study aimed to (1) study the outcomes of intermediate care rehabilitation for post-stroke patients in Mueang Lopburi district, and (2) study factors associated with functional improvement. Methods: A retrospective study collected data from King Narai Hospital’s medical records and the IMC coordination center of King Narai Hospital’s database. The study included post-stroke patients in Mueang Lopburi District, Lopburi Province, from October 1, 2022, to July 31, 2024. The demographic data and clinical data were collected. Functional changes were calculated from Barthel index at admission and at discharge the IMC rehabilitation and analyzed using the paired t-test. Functional gain and rehabilitation effectiveness was calculated. Factors associated with functional improvement were analyzed using Chi-square test, unpaired t-test, Mann-Whitney U test, and logistic regression analysis. Result: The study included 251 patients, 60.6% were males, 69.7% were ischemic stroke and mean age was 64.18 (SD 13.88) years. The mean Barthel Index score significantly improved from 6.44 (SD 4.90) at admission to 16.20 (SD 5.78) at discharge (p<0.001). Mean functional gain and rehabilitation effectiveness was 9.76 (SD 5.95) and 74.86 (SD 36.82), respectively. Multivariate logistic regression analysis revealed that patient who had no complication after stroke was significantly associated with functional improvement (adjusted OR=2.92, 95%CI=1.07-8.00, p=0.037). Conclusion: Following intermediate care rehabilitation, post-stroke patients in Mueang Lopburi district improved in functional outcome. Patient who had no complication after stroke revealed significant association with functional improvement.